Examining the factors impacting small and medium enterprises (SMEs) in accessing development debt finance in the kingdom of Eswatini - Dlamini, Zanele F (Graduate School of Business (GSB), 2021)
SMEs are conduits for the transformation of economies because they act as catalysts for private sector development. However, they face several constraints to accessing finances for their growth and development. Hence, by using a secondary dataset from the Central Bank of Eswatini that comprises 1,390 loan applicants, an empirical analysis was done using a binary logistic regression analysis to assess credit rationing factors preventing SMEs in the Kingdom of Eswatini to access DFIs loans for their growth and development. Thus, the objectives of the study are to examine the relationships between credit rationing factors and their effects on accessing DFI loans in the Kingdom of Eswatini. Descriptive analysis provided an explanation as to how these factors influence the financing of SMEs in the Kingdom of Eswatini. Pearson's correlation coefficient was, therefore, employed to determine the relationships between credit rationing factors and binary logistic regression analysis to examine the effect of these factors on DFIs loans accessibility. This method was used to determine the strength of the relationship between loan access and credit rationing factors. The findings show that the age of SMEs and loan amounts are some of the major negative factors impacting access to DFIs loans in the Kingdom of Eswatini. A mature SME is less constrained to access DFIs loan compared to start-ups and growing SMEs. Furthermore, SMEs that apply for sustainable loans are less constrained to access DFIs loans than those that apply for unsustainable and very high amounts. It is, therefore, concluded that DFIs in the Kingdom of Eswatini apply credit rationing in dispersing loans to SMEs. DFIs should link their loan amount to demands and to the period of existence, as only well established and matured SMEs have an added advantage in accessing DFIs loans. For these reasons, it is recommended that economic policy makers should devise loan access policies that suit start-ups and growing SME for their conducive development and growth. This policy is vital because SMEs have a pivotal role to play in the overall economic growth of the Kingdom of Eswatini.